Pengetahuan Perawat tentang Sasaran Keselamatan Pasien dengan Kepatuhan Melakukan Identifikasi Pasien dengan Benar - Saptomo, Reska Budi; Hamzah, Amir; Ramadhani, Anggun Fajar; Alamsyah, Azhar Zulkarnain (Journal of Telenursing (JOTING), 2026)
This study aims to analyze the relationship between nurses' knowledge of patient safety goals and correct patient identification. The method used is a quantitative study with a cross-sectional approach, sampling was carried out using purposive sampling of 92 respondents, data were collected through questionnaires and analyzed using the Chi-Square test. The results of this study showed a p-value of 0.000 (p < 0.05), which means there is a significant relationship between the level of knowledge and nurse compliance. Nurses with good knowledge tend to be highly compliant (83.6%), while those with sufficient knowledge are more likely to be non-compliant (8.8%). In conclusion, there is a relationship between nurses' knowledge of patient safety goals and compliance in correct patient identification.   Keywords: Patient Identification Compliance, Nurse Knowledge, Patient Safety Goals